Peran Perangkat Desa dan Pemanfaatan Teknologi Informasi terhadap Akuntabilitas Pengelolaan Dana Desa - Rini Dwiyanti; Sjarief Hidajat (IPM2KPE, 2022)
This study aims to examine and prove the influence of the role of village officials and the use of information technology on the accountability of managing village funds in Bakung Pringgodani Village, Balongbendo District, Sidoarjo Regency. The research method used is quantitative method and the data used is primary data. Data collection method in the form of a questionnaire. The population in this study were 45 village officials in Bakung Pringgodani Village, Balongbendo District, Sidoarjo Regency. The sampling method used in this study uses a census or saturated sampling method. The data analysis technique used descriptive statistical analysis which was processed using the SmartPLS 3.0 statistical software. The results showed that a) the variable role of village officials in the accountability variable for managing village funds had a t-statistic value of 3.248 > 1.960 and a p-value of 0.001 <0.05; b) the variable utilization of information technology on the accountability variable for managing village funds has a t-statistic value of 4.116 > 1.960 and a p-value of 0.000 <0.05. In conclusion, the role of village officials and the use of information technology have a positive and significant influence on the accountability of managing village funds in Bakung Pringgodani Village, Balongbendo District, Sidoarjo Regency. Keywords: Village Fund Management Accountability, Village Devices, Information Technology